Effects of Hydroclimatic Variability on the Spatial Dynamics of Ponds (Simenti, Kountadala and Oudassi) of the Gambia River Basin in the Niokolo Koba National Park (Senegal) - Faye, Cheikh; Solly, Boubacar; Sané, Bouly; Cissé, AIssatou (International Journal of Geography and Geology, 2019)
With climate change, West African watercourses have undergone profound changes with large runoff deficits, faster dryings and very severe low flows. These modifications have led to a sharp decrease in water resources and a drying up of some water bodies. This article evaluated the effects of hydroclimatic variability on the spatial dynamics of a few ponds (Simenti, Kountadala and Oudassi) in the Gambia Basin in the Niokolo Koba National Park, NKNP, (Senegal). Data from five sets of images are used for pond trend mapping (Landsat, Google Earth and Sentinel). The hydroclimatic data used in this study include precipitation, temperature, evaporation, and discharge data from the Gambia Basin subjected to trend (Mann-Kendall) and rupture (Pettitt) tests. The results show that the trend is positive and significant for temperatures and evaporation and negative and significant for precipitation at a 95% confidence level. The surface area of the ponds, from 40.3 ha in 1975, increased sharply to 79.3 ha in 1988, then rose slightly in 1999 with 80.2 ha and in 2010 with 83.4 ha before to shrink sharply from 67.8 ha in 2019 due to rainfall deficit and the expansion of aquatic vegetation. Recommendations were made on how to improve the problem. Faced with the scarcity and drying up of water in these ponds of Niokolo Koba Park, water transfer operations such as those noted with the Simenti pond to save animals, remain fundamental according to some conservatives.